2022
DOI: 10.1177/08982643221101352
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neighborhood Physical Disorder and Social Cohesion on Racial and Ethnic Disparities in Dementia Risk

Abstract: Objectives: To analyze how neighborhood physical disorder and social cohesion are associated with racial and ethnic disparities in dementia risk. Methods: Nine years of data (2011–2019) were retrieved from the National Health and Aging Trends Study, a nationally representative U.S. older adult (age 65+) sample. Cox regression analyzed time to dementia diagnosis using composite scores for neighborhood physical disorder and social cohesion. Results: Higher baseline neighborhood physical disorder (Adjusted Hazard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…All covariates were selected based on prior research on dementia risk factors, 17 and a comparable study using this data set for dementia research. 18 Sociodemographic covariates included age, gender (male or female), race and ethnicity (non-Hispanic White, non-Hispanic Black, Hispanic, Asian, or Other), highest level of education (less than high school, high school, or college), total household income, marital status (married or unmarried), and metropolitan residence (metro or non-metro).…”
Section: Methodsmentioning
confidence: 99%
“…All covariates were selected based on prior research on dementia risk factors, 17 and a comparable study using this data set for dementia research. 18 Sociodemographic covariates included age, gender (male or female), race and ethnicity (non-Hispanic White, non-Hispanic Black, Hispanic, Asian, or Other), highest level of education (less than high school, high school, or college), total household income, marital status (married or unmarried), and metropolitan residence (metro or non-metro).…”
Section: Methodsmentioning
confidence: 99%
“…Because there may be unmeasured race/ethnicity-specific contextual factors that shape domains of cognitive function, additional research is needed to explore potential differences in the relationship between neighborhood factors and cognition across and within racial/ethnic groups. For example, Wong and Wang (2022) found that greater perceived physical disorder was associated with lower risk of dementia among Hispanic older adults, which may be explained by cognitive health-promoting factors such as multilingualism, strong family ties, and community supports. Additionally, researchers have discussed that racial/ethnic differences in semantic memory and vocabulary may be due to varying social contextual experiences that are linked to inequitably restricted social determinants of health, such as educational attainment and economic advantage, among marginalized groups (Meyer et al, 2018; Sisco & Marsiske, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Racial/ethnic disparities in both exposure to different neighborhood environments as well as in cognitive function are documented (Thierry et al, 2021; Wong & Wang, 2022). To our knowledge, the scope of existing research addressing how race and ethnicity may factor into associations between neighborhood characteristics and cognition has not yet been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…13 By contrast, Hispanic older adults with dementia may have had increased odds of COVID-19 because they had the lowest income and highest prevalence of ADL limitations compared with both older White and Black adults in our sample. 14 In fact, a recent study indicated that relative to White older adults, although the odds of COVID-19 were higher for Asian (aOR = 1.68, P = 0.61) and Black (aOR = 1.13, P = 0.73) respondents, they were significantly higher for only Hispanic (aOR = 2.71, P < 0.01) respondents in the NHATS COVID-19 sample. 11 Healthcare professionals should therefore take note that Hispanic older adults may have elevated odds of COVID-19, especially those with dementia, based on our current findings.…”
Section: Dementia Statusmentioning
confidence: 90%